2019
DOI: 10.1111/jocn.14834
|View full text |Cite
|
Sign up to set email alerts
|

Nursing people with intellectual disability and dementia experiencing pain: An integrative review

Abstract: Aims and objectives To explore the current evidence of nurses caring for people with intellectual disability and dementia who experience pain. Background People with intellectual disability are ageing and are experiencing age‐related health conditions including dementia and conditions associated with pain, but at an earlier age. Addressing the needs of people with intellectual disability who develop dementia is a new challenge for nurses. Design An integrative literature review. Methods A systematic search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
0
15
0
2
Order By: Relevance
“…A further study of ED encounters by Fry, Arendts, Chenoweth, and MacGregor (2015) also identified the older person with a cognitive impairment as likely to experience an even longer delay receiving analgesia than those older persons who were cognitively intact. An integrated review by Dillane and Doody (2019) on the older person with intellectual disability and advanced dementia identified often their pain is also unrecognised.…”
Section: Introductionmentioning
confidence: 99%
“…A further study of ED encounters by Fry, Arendts, Chenoweth, and MacGregor (2015) also identified the older person with a cognitive impairment as likely to experience an even longer delay receiving analgesia than those older persons who were cognitively intact. An integrated review by Dillane and Doody (2019) on the older person with intellectual disability and advanced dementia identified often their pain is also unrecognised.…”
Section: Introductionmentioning
confidence: 99%
“…For all but two participants, the use of HR monitoring led to some change in caregivers' understanding of the participant. 17,27,28 HR monitoring may improve this situation.…”
Section: Change Of Care Practice Following Hr Monitoringmentioning
confidence: 99%
“…[8][9][10] In the majority of cases, the condition is evident early in life. Approximately 5% of persons with ID have severe ID (IQ: [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] or profound ID (IQ < 20). 11,12 These patients are entirely dependent on their caregivers, but intellectual shortcomings limit their ability to communicate with them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to frequent co-morbid conditions that involve pain, pain is highly prevalent in persons with dementia and with other diseases that cause cognitive impairment or difficulty expressing pain, such as intellectual disability [1][2][3][4]. Various dementia types may differently affect the way pain is being perceived (threshold and intensity), processed, and communicated, but typically about half of persons with dementia are in pain [1,5,6].…”
Section: Introductionmentioning
confidence: 99%